Análisis técnico para la construcción de una planta de generación solar para JASEC - Barrantes-Monge, Jorge Isaac (Instituto Tecnológico de Costa Rica, 2018)
In this work, a feasibility study is developed that focuses on the design of a photo-voltaic solar power plant, using mono-crystalline panels with bifacial technology, in an empty area of the JASEC company. The project will be connected to the distribution network of said company at medium voltage at 34.5 KV. In the project, a study is made of the technical regulations and laws that regulate the energy sector, especially the photovoltaic market in Costa Rica. To obtain the global solar radiation that exists in the environment and some other important meteorological data, a prediction model of irradiation, technical studies and satellite databases was made. The final design consists of 2540 mono-crystalline panels mounted on metal structures at 10º with respect to the south and 12º with respect to the azimuth, with 5264 m2 of covered area, it has 17 inverters and a single transformer for the plant with an installed power of 1MW in the generator. The system has a P.R. (Power ratio) of 0.806% and an annual efficiency of 19.3%, delivering 1,176 MWh per year to the network. The investment required is around $ 1,403,887.99, which included operating expenses, maintenance, policy, geotechnical studies, in-creases in energy and transportation costs. The financing is made through a loan with an annual interest of 8.5% with a term of 10 years. The economic results show that the project is feasible, with a VAN (net present value) of $ 1,976,781.83 and an TIR (internal rate of return) of 16.07% at the end of the 25 years of useful life.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2018.
Keywords: Redes de distribución; Energía; Plantas; Técnica; Modelos; Predicciones; Radiación; Factores; Rendimiento; TIR; VAN; Research Subject Categories::TECHNOLOGY::Engineering mechanics